Clinical Progress in Mesenchymal Stem Cell Therapy: A Focus on Rheumatic Diseases - Helal F. Hetta; Alaa Elsaghir; Victor Coll Sijercic; Abdulrahman K. Ahmed; Sayed A. Gad; Mahlet S. Zeleke; Fawaz E. Alanazi; Yasmin N. Ramadan (Immunity, Inflammation and Disease)
ABSTRACT Background Rheumatic diseases are chronic immune‐mediated disorders affecting multiple organ systems and significantly impairing patients' quality of life. Current treatments primarily provide symptomatic relief without offering a cure. Mesenchymal stem cells (MSCs) have emerged as a promising therapeutic option due to their ability to differentiate into various cell types and their immunomodulatory, anti‐inflammatory, and regenerative properties. This review aims to summarize the clinical progress of MSC therapy in rheumatic diseases, highlight key findings from preclinical and clinical studies, and discuss challenges and future directions. Methodology A comprehensive review of preclinical and clinical studies on MSC therapy in rheumatic diseases, including systemic lupus erythematosus, rheumatoid arthritis, ankylosing spondylitis, osteoarthritis, osteoporosis, Sjögren's syndrome, Crohn's disease, fibromyalgia, systemic sclerosis, dermatomyositis, and polymyositis, was conducted. Emerging strategies to enhance MSC efficacy and overcome current limitations were also analyzed. Results and Discussion Evidence from preclinical and clinical studies suggests that MSC therapy can reduce inflammation, modulate immune responses, and promote tissue repair in various rheumatic diseases. Clinical trials have demonstrated potential benefits, including symptom relief and disease progression delay. However, challenges such as variability in treatment response, optimal cell source and dosing, long‐term safety concerns, and regulatory hurdles remain significant barriers to clinical translation. Standardized protocols and further research are required to optimize MSC application. Conclusion MSC therapy holds promise for managing rheumatic diseases, offering potential disease‐modifying effects beyond conventional treatments. However, large‐scale, well‐controlled clinical trials are essential to establish efficacy, safety, and long‐term therapeutic potential. Addressing current limitations through optimized treatment protocols and regulatory frameworks will be key to its successful integration into clinical practice.